2001
DOI: 10.1103/physrevb.63.193408
|View full text |Cite
|
Sign up to set email alerts
|

Real-space representation of electron localization and shell structure in jelliumlike clusters

Abstract: Results of first-principles calculations on pure and doped aluminum clusters are analyzed using the electron localization function ͑ELF͒ to obtain a real-space representation of the electronic shell structure. Our results provide a quantitative analysis of the bonding nature and localization of charge in jelliumlike metal clusters and show that similar to atoms, ELF reproduces the electronic shell structure of clusters in real space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 19 publications
8
30
1
Order By: Relevance
“…In particular, the electronic charge forms a framework throughout the cluster with the highest densities located in the interstitial regions. This corresponds with development of metallic or Jelliumlike bonding and compares well with earlier studies of Al 13 , Al 13 -and Al 12 Si [39][40][41][42][43]. As reported previously this is also evidenced by the high degree of degeneracy in the eigenvalue spectrum of endo-Ga 12 C [19,44].…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…In particular, the electronic charge forms a framework throughout the cluster with the highest densities located in the interstitial regions. This corresponds with development of metallic or Jelliumlike bonding and compares well with earlier studies of Al 13 , Al 13 -and Al 12 Si [39][40][41][42][43]. As reported previously this is also evidenced by the high degree of degeneracy in the eigenvalue spectrum of endo-Ga 12 C [19,44].…”
Section: Resultssupporting
confidence: 76%
“…In addition to the delocalised framework, there is significant charge concentrated about the core atom of these endo-Ga 12 X clusters. Sun et al [42] noted similar behaviour for Al 12 Si, with the excess charge from the core silicon atom distributed in bonds between the core and the cage Al atoms. As the electronegativity of the core atom increases these regions of electron density become more contracted.…”
Section: Resultsmentioning
confidence: 62%
“…The distance of Na to the four O atoms is rather small (2.3 Å), enabling strong electron transfer between Na and O. We then profiled the electron localization function (ELF) to provide an intuitive mapping of electron localization within the network, [29][30][31][32] further confirming the Na-O ionic bonding. At a higher annealing temperature (∼410 K), the porous network is transformed into a closepacked new phase (Figure 3a).…”
Section: Resultsmentioning
confidence: 88%
“…[16]. However, it has been found recently that C 60 cannot be used to stabilize Si 60 , while the magic clusters with 40 electrons such as Al 12 X (X ¼ Si, Ge, Sn, Pb) will do [17], because the magic cluster can be used as a superatom [18]. As for the one-dimensional Si structure, we found that the tube-like Si 12 W cluster cannot be used as the building block for the construction of 1D Si nano-structure [19], while encapsulating Si clusters into carbon nano-tube can fabricate onedimensional Si structure, and change effectively the electronic and optical properties of the system [20].…”
Section: Discussionmentioning
confidence: 99%